2021
DOI: 10.1079/cabicomm-62-8157
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Effects of Village Based Plant Clinic Service in Selected Regions of Ethiopia

Abstract: This study examined the effects of pest management advice given at village-based plant clinics in selected regions of Ethiopia on three key crops grown and brought to plant clinics in the study areas: maize, potato and tomato. The results showed that while there is reduction in use of pesticides among farmers, which can be taken as a positive outcome, there has been an increasing trend in the use of other inputs such as fertilizer and improved seed varieties. Farmers demonstrated better knowledge and practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…In the interviews key informants indicated that most farmers seek advisory information on how to carry out crop protection therefore acquire knowledge and skills on guidance about the cultural and agronomic aspects of farming seed treatment, required seed rate, technical advice on sowing time and seed bed preparation, management of pests and diseases. This result agrees with those of Bundi [36] who found out that farmers had access to various type of advisory information from plant health clinic that help in promoting of crop production in Ethiopia.…”
Section: Type Of Advisory Information Access On Potato Healthsupporting
confidence: 91%
See 1 more Smart Citation
“…In the interviews key informants indicated that most farmers seek advisory information on how to carry out crop protection therefore acquire knowledge and skills on guidance about the cultural and agronomic aspects of farming seed treatment, required seed rate, technical advice on sowing time and seed bed preparation, management of pests and diseases. This result agrees with those of Bundi [36] who found out that farmers had access to various type of advisory information from plant health clinic that help in promoting of crop production in Ethiopia.…”
Section: Type Of Advisory Information Access On Potato Healthsupporting
confidence: 91%
“…According to Rebecca [38] farmers access to advisory service strongly suggests that most of the respondents are likely working in conjunction with an extension agent therefore utilizing advisory services that improve crop production. These results are also sturdy with the findings of Bundi [36] who found out that type of information access from plant health clinic advisory services favorably influence potato, maize and tomato production in Ethiopia. He stated that farmers who accessed this advisory information had more knowledge related to pests and diseases management and knew more about new technologies in crop production.…”
Section: Influence Of Plant Health Clinic Advisory Services On Potato...supporting
confidence: 81%